Zur Fertilität und Mortalität der Chrysomeliden Diabrotica balteata Lec., Andrector ruficornis (Oliv.) und Systena basalis Duval (Coleoptera, Chrysomelidae). - Heyer, Wolfgang; Chiang Lok, Maria Luisa; Cruz, Bienvenido (Contributions to Entomology = Beiträge zur Entomologie, 1993)
In connection with investigations of the population dynamics of bean pests in Cuba were made experiments on the fertility and mortality of Diabrotica balteata, Andrector ruficornis and Systena basalis. The highest fertility was recorded for D. balteata (maximal 600 eggs). The life time reached approximately 20 days. Females of the species A. ruficornis had an egg - production of 335 eggs when reaching a life time of 89 days. The mentioned numbers refer to laboratory reared individuals. Beetles collected in the fields at beginning of the vegetation period had a lower fertility, i.e. approximately 33 and 63 % of the above mentioned. Fertility was lowest with field - collected individuals (23,8 eggs / female) of S. basalis.